1998
DOI: 10.1152/ajpcell.1998.275.2.c475
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial gene reprogramming associated with a cardiac cross-resistant state induced by LPS preconditioning

Abstract: Lipopolysaccharide (LPS) preconditioning induces cardiac resistance to subsequent LPS or ischemia. This study tested the hypothesis that resistance to LPS and resistance to ischemia are two manifestations of cardiac cross-resistance which may involve reprogramming of cardiac gene expression. Rats were preconditioned with a single dose of LPS (0.5 mg/kg ip). Cardiac resistance to LPS was examined with a subsequent LPS challenge. Cardiac resistance to ischemia was determined by subjecting hearts to ischemia-repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…7B). A similar LPS-induced cardiac cross-resistance to ischemia has been reported previously (23) and had shown that LPS preconditioning induces cardiac resistance to subsequent ischemia. Our findings suggested a similar LPS preconditioning of mouse lung-specific Mig-6 expression in response to MV.…”
Section: Discussionsupporting
confidence: 83%
“…7B). A similar LPS-induced cardiac cross-resistance to ischemia has been reported previously (23) and had shown that LPS preconditioning induces cardiac resistance to subsequent ischemia. Our findings suggested a similar LPS preconditioning of mouse lung-specific Mig-6 expression in response to MV.…”
Section: Discussionsupporting
confidence: 83%
“…Since it was previously shown that endothelial cells (EC) express PPARs (31), accumulating interests were focused on the anti-inflammatory effects of PPAR agonists on the vascular tissue. In addition, it was revealed that the activation of PPAR-␥ with its agonists effectively attenuates inflammatory processes in a number of organs such as heart (32)(33)(34)(35), kidney (36,37), lung (38), and intestine (15, 39) against ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms known to mediate endotoxin tolerance in macrophages that lead to suppression of specific cytokines and inflammatory molecules involve attenuation of NF-κB and AP-1 (activator protein 1) and enhanced expression of the signalling mediators IRAK-M (interleukin-1-receptor-associated kinase M) and SOCS-1 (suppressor of cytokine signalling 1) [48,49]. A case for gene reprogramming can also be made where preconditioning with LPS induces cardiac resistance to ischaemia [50]. In this scenario, exposure to LPS may induce non-specific myocardial adaptations through gene changes (e.g.…”
Section: Reprogramming the Genomic Response To Injury: A Proposed Mecmentioning
confidence: 99%